A case of measles in a Nepalese child: where are we failing? - Lageju, Nimesh; Neupane, Durga; Jaiswal, Lokesh Shekher; Jha, Ashish Kumar; Rawat, Roshan (International Journal Of Community Medicine And Public Health, 2022)
Measles affected more than 90% of children under 15 years of age and caused 2-3 million measles-associated deaths globally each year before the introduction of vaccines against it. Today, measles vestiges a leading cause of vaccine-preventable illness worldwide, causing more than 100,000 deaths annually. Characterized by a febrile rash illness, measles is often self-resolving. However, significant complications can occur including encephalitis with permanent neurologic sequelae and death in one to three out of 1000 measles cases. Although global measles elimination is a WHO goal, current trends in the epidemiology of measles and vaccine hesitancy suggest that this goal is not yet attainable. As the most highly transmissible vaccine-preventable disease, measles is especially subtle to changes in herd immunity, the impact of vaccine refusal and globalization.